A Genetic Model Reveals Biological Features of Neonatal CD4 Helper Cells Undergone Homeostasis in Mice - Lei, Lei; Zhang, Xingzhe; Yang, Xiaofeng; Su, Yanhong; Liu, Haiyan; Yang, Hang; Wang, Jinli; Zou, Yujing; Wang, Xin; Jiao, Anjun; Zhang, Cangang; Zheng, Huiqiang; et al. (Frontiers in Cell and Developmental Biology, 2021)
CD4+ T cells are essential for regulating effective immune response to pathogens and immune balance. Recent studies have demonstrated the unique features of T cells in neonate mice, such as more sensitive to antigen response and preference toward T helper 2 (Th2) response and regulatory T cells (Tregs) differentiation. However, the biological characteristics of neonatal age-derived CD4+ T cells following homeostasis remain unclear. Here we utilized a lineage tracing model of TCRδCreERR26ZsGreen to mark neonatal- and adult-derived CD4+ T cells followed by a combination analysis of activation, proliferation, survival, and differentiation. Our results showed that neonatal CD4+ T cells had higher capacity of activation, proliferation, apoptosis, and differentiation toward Th2 and T helper 17 (Th17) lineages, accompanied by a reduced potential for T helper 1 (Th1), T helper 9 (Th9), and Treg lineages. In contrast, tracked neonatal CD4+ T cells exhibited similar characters of above-mentioned of tracked adult cells in adult mice. Therefore, our data support a natural requirement for CD4+ T cells to acquire fully-equipped functional potentials of adult cells.